Comparative study of “Linux server” and “Microsoft server” - M. Alfakhri, Ibrahem (The Libyan International Medical University - Faculty Of Information Technology, 2021)
A server is a computer designed to process requests and deliver data to another computer over the internet or a local network. Although any computer running the necessary software can function as a server, the most typical use of the word references the enormous, highpowered machines that function as the pumps pushing and pulling data from the internet. Most computer networks support one or more servers that handle specialized tasks. As a rule, the larger the network in terms of clients that connect to it or the amount of data that it moves, the more likely it is that several servers play a role, each dedicated to a specific purpose. There are many servers in networking which are divided into “open source” such as Linux Ubuntu and “commercial” such as Windows Server. This study compares the two to reach a clear conclusion of which one is better than the other according to a specific criterion used in this project.